Epilepsy adverse events post vaccination - Darrell O. Ricke (Exploration of Neuroscience, 2024)
Aim: Seizure and epilepsy adverse events (AEs) can occur following vaccination. For epilepsy AEs, they are generally expected to only occur at background population frequencies without associations with immunizations. The Vaccine AEs Reporting System (VAERS) collects a subset of AEs experienced by vaccinees, including multiple epilepsy related AEs. This study examines the possibility of immunization associated epilepsy AEs in VAERS occurring above background rates. Methods: Herein, VAERS is retrospectively examined for epilepsy and seizure AEs following immunizations (AEFIs). Reported AEFIs are normalized by total AEFIs for each vaccine. VAERS data is examined by vaccine type, vaccine source, vaccinee gender, and age-stratified for infants. Results: Association signals for examined epilepsy and seizure AEFIs are identified for multiple vaccines when compared to other vaccines with normalized frequencies above expected population background frequencies. Normalized epilepsy AEFI frequencies for children less than 1 year are higher than children aged 1 year for several vaccines. For pairs of matched vaccines from different manufacturers, statistically different epilepsy AEFI normalized frequencies were observed. These matched pairs for multiple vaccines implicate likely vaccine contaminations (e.g., endotoxins) as likely candidates for causing elevated epilepsy and seizure AEFIs. Conclusions: Based on the reported results, delaying some immunizations of a small set of vaccines until children are 1 year of age is predicted to reduce epilepsy AEFI occurrences for these vaccines. For several vaccines, statistically significant differences in epilepsy AEFI normalized frequencies were detected for the same (or similar) vaccine from different manufacturers; this suggests that possible manufacturing contaminant(s) (e.g., endotoxins) as the likely causative agent(s) for observed epilepsy AEFIs above background rates. Eliminating or reducing these possible contaminants is predicted to reduce the observed associations closer to background population levels observed for other vaccines with very low epilepsy AEFI normalized frequencies.